Hope, disappointment and perseverance: Reflections of people with Myalgic encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and Multiple Sclerosis participating in biomedical research. A qualitative focus group study - Lacerda, Eliana M.; McDermott, Clare; Kingdon, Caroline C.; Butterworth, Jack; Cliff, Jacqueline M.; Nacul, Luis (Health expectations : an international journal of public participation in health care and health policy, 2019)
Background The Clinical Understanding and Research Excellence in ME/CFS group (CureME) at the London School of Hygiene & Tropical Medicine has supported and undertaken studies in immunology, genetics, virology, clinical medicine, epidemiology and disability. It established the UK ME/CFS Biobank (UKMEB), which stores data and samples from three groups: participants with ME/CFS, Multiple Sclerosis (MS) and healthy controls. Patient and public involvement have played a central role from its inception. Aim To explore the views of participants with ME/CFS and MS on CureME research findings, dissemination and future biomedical research priorities. Method Five ME/CFS and MS focus groups were conducted at two UK sites. Discussions were transcribed and analysed thematically. Results A total of 28 UKMEB participants took part: 16 with ME/CFS and 12 with MS. Five themes emerged: (a) Seeking coherence: participants’ reactions to initial research findings; (b) Seeking acceptance: participants explore issues of stigma and validation; (c) Seeking a diagnosis: participants explore issues around diagnosis in their lives; (d) Seeking a better future: participants’ ideas on future research; and (e) Seeking to share understanding: participants’ views on dissemination. Focus groups perceived progress in ME/CFS and MS research in terms of “putting together a jigsaw” of evidence through perseverance and collaboration. Conclusion This study provides insight into the emotional, social and practical importance of research to people with MS and ME/CFS, suggesting a range of research topics for the future. Findings should inform biomedical research directions in ME/CFS and MS, adding patients’ voices to a call for a more collaborative research culture.